Development of E-LKPD Using Canva Based on Problem-Based Learning on Respiratory Material to Improve Critical Thinking Skills and Learning Outcomes of Elementary School Students - Siti Khodijah Khodijah; Slamet Hariyadi; Jekti Prihatin (PROGRAM STUDI PENDIDIKAN BIOLOGI FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN UNIVERSITAS JEMBER, 2025)
This study aims to develop e-LKPD based on Problem-Based Learning (PBL) using Canva on the respiratory system material of fifth grade elementary school students. The background of this study is based on the low critical thinking skills and learning outcomes of students due to the dominance of lecture methods and limited interactive digital learning media. This study uses the Research and Development (R&D) method with the ADDIE model which includes the stages of analysis, design, development, implementation, and evaluation. The validation results show that e-LKPD is declared very valid by material experts (95%), media experts (89%), and practitioners (100%). The practicality test shows the implementation of learning above 87% and very good student responses above 95%. The effectiveness of the product is evidenced by a significant increase in learning outcomes, with an N-Gain value between 0.71 and 0.73 (high category). In addition, indicators of students' critical thinking skills have increased in all aspects after the implementation of e-LKPD. Thus, the PBL-based e-LKPD using Canva that was developed is declared valid, practical, and effective in improving critical thinking skills and learning outcomes of elementary school students.